PENGARUH RESILIENSI MATEMATIS DAN SELF CONFIDENCE TERHADAP HASIL BELAJAR SISWA KELAS V DI UPT SPF SD NEGERI MANGASA - Muhammad Asfan As; Ahmad Syamsuadi; Sirajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of mathematical resilience and self-confidence on the mathematics learning outcomes of fifth-grade students at UPT SPF SD Negeri Mangasa. The background of this research emphasizes the importance of psychological factors in supporting students’ success in learning mathematics,  This research employed an ex post facto approach with a correlational design. The subjects were all 38 fifth-grade students, selected using total sampling. Data were collected through Likert-scale questionnaires to measure mathematical resilience and self-confidence, as well as a mathematics achievement test to assess learning outcomes. Data analysis included descriptive and inferential statistics, such as tests of normality, linearity, classical assumptions, and multiple linear regression.The results indicate that mathematical resilience and self-confidence simultaneously have a significant effect on students’ learning outcomes, as shown by the F-test significance value of 0.000 (<0.05). The coefficient of determination (R²) of 0.438 suggests that these two variables contribute 43.8% to the variation in learning outcomes. Partially, both mathematical resilience and self-confidence have a positive and significant effect on learning outcomes, supported by t-test results with significance values <0.05. These findings highlight the importance of enhancing students’ resilience and self-confidence to improve mathematics learning outcomes. Therefore, teachers are encouraged to implement instructional strategies that strengthen these aspects.